Investment issues in relations between the PRC and EU - Zhumagalieva, Ж.Ә.; Birimkulova , Г.У. (Bulletin of the L.N. Gumilyov Eurasian National University. Political Science. Regional Studies. Oriental Studies. Turkology Series., 2023)
The article discusses the role of direct investment in cooperation between China and EU member states. China’s role as a global investor and financier has grown rapidly in recent decades. The bilateral investment agreement opens up great opportunities for both parties. Currently, cooperation in this area is regulated by bilateral agreements between states. In addition, today China is stepping up the promotion of the “One Belt, One Road” initiative, one of the ultimate goals of which is Europe. However, China’s somewhat increased investment in the European Union has generated much controversy. This highlights China’s desire to take over the European economy. The purpose of the work is to analyze the investment policy of China and the countries of the European Union and determine its features. When writing the article, qualitative, quantitative and comparative analyzes of scientific research were used. In the course of the study, the history of the development of investment relations between the two parties was studied and its current state was analyzed. In recent years, writers have focused on the “Global Gate” initiative to slow down China’s influence in the European Union. This article aims to carefu